The Commercial Use of Biodiversity: Access to Genetic Resources and Benefit Sharing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Commercial Use of Biodiversity: Access to Genetic Resources and Benefit Sharing K Ten Kate and SA Laird. Earthscan. 1999. 416 pp. ISBN 1 85383 334 7 £50 81.10 Earthscan Publications Limited, 120 Pentonville Road, London N1 9JN, UK. Fax: